PENGARUH KOMPETENSI AUDITOR, INDEPENDENSI AUDITOR, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT (Studi Kasus Pada Kantor Akuntan Publik Di Kota Jakarta) - Eka Rahim, Sabna; Dewi Astuti, Tutut (JURNAL ILMIAH EDUNOMIKA, 2025)
This research was conducted to determine, test, and analyze the influence of auditor competence, auditor independence, and auditor integrity on audit quality (a case study of public accounting firms in Jakarta). The population in this study was public accountants working at seven Public Accounting Firms (KAP) in Jakarta. The data analysis technique used SPSS. The SPSS output shows that audit competence significantly influences audit quality and auditors' skills and knowledge in carrying out their duties. The results indicate that auditor independence does not considerably influence audit quality. If autonomy is compromised, the possibility of bias and errors in financial statements will increase. The analysis results indicate that integrity significantly influences audit quality, where auditors with a high level of integrity tend to provide more reliable and standard-compliant reports. Furthermore, the calculation results show that the F-significance level is less than 0.05, indicating that the overall regression model has sufficient explanatory power in explaining the dependent variable, namely, audit quality.